In a nutshell: Caribbean Agriculture & the WTO Agreements - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2022)
This issue of "In a Nutshell" focusses on the 1994 GATT / WTO Agricultural Agreements of the Uruguay Round wich are relevant to global agricultural trade.